The effects of greenwashing on consumer behavior in the fashion industry: a study comparing the fast fashion and luxury fashion industry - literature review part 3 - Mooslechner, Hannah (2023)
This thesis examines the effects of greenwashing on consumer behavior, focusing on the comparison between the luxury and fast fashion industries. A research gap was identified by the analysis of existing literature, indicating that there are substantially fewer greenwashing allegations against luxury fashion brands. This imbalance is further reflected in the amount of existing literature. Moreover, previous research has not yet provided a comparison regarding the effects of greenwashing in these sectors. Thus, this study makes a valuable contribution by revealing that greenwashing has more severe negative effects on consumer behavior in the luxury than in the fast fashion sector.